Ibu Pejabat Polis Bukit Aman - Hairol Azmi, Muhammad Hafiz; Zulkarnain, Nurul Izzah; Razak, Ayu Nadhirah; Abdullah, Nur Atirah (2024)
The Royal Malaysian Police Headquarters Complex is located in Bukit Aman. The Inspector General of Police, the Deputy Inspector General of Police, and the PDRM Directors of the Management Department, the Criminal Investigation Department (JSJ), the Department of Internal Security and Public Order (KDN/KA), the Narcotics Crime Investigation Department (JSJN), the Investigation Department Commercial Crime (JSJK), Special Branch, and Special Task Force are also located here. Policies, directives, and commands for the whole police force are developed and issued from Bukit Aman. What is more crucial is the location of the Malaysian Control Centre (Malaysia Control Centre - MCC), which can be defined as the country's heart.